Bridging the age gap in breast cancer: evaluation of decision support interventions for older women with operable breast cancer: protocol for a cluster randomised controlled trial - Collins, Karen; Reed, Malcolm; Lifford, Kate; Burton, Maria; Edwards, Adrian; Ring, Alistair; Brain, Katherine; Harder, Helena; Robinson, Thompson; Cheung, Kwok-Leung; Morgan, Jenna; Audisio, Riccardo; et al. (BMJ Publishing Group, 2017)
Introduction: While breast cancer outcomes are improving steadily in younger women due to advances in screening and improved therapies, there has been little change in outcomes among the older age group. It is inevitable that comorbidities/frailty rates are higher, which may increase the risks of some breast cancer treatments such as surgery and chemotherapy, many older women are healthy and may benefit from their use. Adjusting treatment regimens appropriately for age/comorbidity/frailty is variable and largely non-evidence based, specifically with regard to rates of surgery for operable oestrogen receptor-positive disease and rates of chemotherapy for high-risk disease.